TRANSFORMATIVE SHIFTS IN RELIGIOUS AFFILIATION: ANALYZING SOCIAL RESPONSES TO USTAZ HANAN ATTAKI'S TRANSITION FROM INDIVIDUAL AUTHORITY TO NAHDLATUL ULAMA (NU) MEMBERSHIP IN INDONESIA - MD, Moh Muafiqul Khalid (Jurnal Sosiologi Reflektif, 2023)
Religious social actors exert significant influence in disseminating their ideas to the public. The people has responded to the movement in religious organisation allegiance from Ustaz Hanan Attaki (UHA) to NU. The objective of this study is to examine the reaction to UHA's shift in religious affiliation, focusing on its impact on Indonesian millennials, who constitute a significant portion of its fan base, as well as the underlying reasons behind this transition. The study employed a qualitative methodology, utilising data retrieval techniques on popular social media platforms such as Instagram and Youtube. The author contends that this shift in affiliation direction demonstrates the robustness of traditional religious authority in Indonesia, where religious actors such as ustaz wield significant influence over societal religious transformation. The results suggest that UHA joined NU with the intention of broadening her activity in preaching the notion of hijrah. By affiliating with NU, he saw a chance to mitigate the past resistance encountered in East Java. This action ultimately elicited both positive and negative reactions from UHA followers on the internet, but it did not demonstrate any signs of causing conflict or exerting influence on the decision to alter UHA's religious affiliation.Aktor sosial keagamaan memegang peranan penting dalam mempromosikan ideologi mereka kepada khalayak. Fenomena bergesernya afiliasi ormas keagamaan dari sosok Ustaz Hanan Attaki (UHA) ke NU telah menimbulkan sejumlah respon dari masyarakat. Penelitian ini bermaksud untuk menganalis respon perubahan afiliasi keagamaan UHA sebagai actor yang sangat popular khususnya di kalangan milineal Indonesia dan apa motif dibalik perubahan afiliasi tersebut. Penelitian dilakukan dengan menggunakan metode kualitatif melalui penelusuran data-data di sosial media seperti Instagram dan Youtube. Penulis berargumen bahwa perubahan arah afiliasi ini menunjukkan kekuatan otoritas tradisional keagamaan di Indonesia, dimana actor keagamaan seperti ustaz menjadi tokoh yang sangat berpengaruh dalam perubahan sosial keagamaan di masyarakat. Hasil mengindikasikan bahwa UHA bergabung ke NU karena ingin memperluas lahan garap konsep hijrah dalam dakwahnya, dengan bergabung ke NU ada peluang untuk mereduksi penolakan dakwahnya yang pernah terjadi sebelumnya di Jawa Timur. Perpindahan ini pada akhirnya memunculkan respon pro dan kontra di kalangan netizen pengikut UHA, namun demikian tidak menunjukkan adanya indikasi konflik maupun pengaruh atas keputusan perubahan afiliasi keagamaan UHA.